Black‐Yellow Bandgap Trade‐Off During Thermal Stability Tests in Low‐Temperature Eu‐Doped CsPbI3. Issue 6 (10th March 2022) - Valastro, Salvatore; Mannino, Giovanni; Smecca, Emanuele; Bongiorno, Corrado; Sanzaro, Salvatore; Deretzis, Ioannis; La Magna, Antonino; Jena, Ajay Kumar; Miyasaka, Tsutomu; Alberti, Alessandra
Abstract : The black γ‐phase of CsPbI3 with its bandgap at ≈1.75 eV can enable the take‐off of tandem solar cells as soon as intrinsic instability to the yellow δ‐phase is solved. Here, a black γ‐phase is formed at low temperature (80–90 °C) by incorporating Eu through EuCl3 or EuI2 . It is forced to become yellow by thermal heating under nitrogen. It is demonstrated how spectroscopic ellipsometry and the related critical points analysis provide a new diagnostic tool to monitor the transformation through the bandgap footprint. As two sides of the same coin, the consumption of the black γ‐phase and the growth of the yellow δ‐phase are addressed and modeled in the range of 60–100 °C using the Avrami's theory. This approach allows extracting the activation energies of the phase transformation that are 0.95 eV versus 1.15 eV using EuI2 and EuCl3, respectively. In situ transmission electron microscopy analyses combined with fast marching simulations highlight that the phase transformation occurs through constant nucleation and growth. Europium has indeed the capability to tackle those processes and to extend the durability of the black γ‐phase at 30 °C in N2 to ≈250 days, hugely above the one observed without Eu (≈hours). Abstract : Two sides of the same coin: the yellow δ‐phase grows over time at the expense of the black γ‐phase, following an Avrami like pathway after an incubating delay time. This kinetic study versus temperature has a predictive valence and allows identifying the beneficial role of Eu in stabilizing the black γ‐phase in the range 30–100 °C.